2023
DOI: 10.1212/wnl.0000000000207917
|View full text |Cite
|
Sign up to set email alerts
|

Association of Sleep Disturbances With Brain Amyloid and Tau Burden, Cortical Atrophy, and Cognitive Dysfunction Across the AD Continuum

So Hoon Yoon,
Han-Kyeol Kim,
Jae-Hoon Lee
et al.

Abstract: Background and ObjectivesPatients with Alzheimer’s disease (AD) frequently suffer from various sleep disturbances. However, how sleep disturbance is associated with AD and its progression remains poorly investigated. We investigated the association of total sleep time with brain amyloid and tau burden, cortical atrophy, cognitive dysfunction, and their longitudinal changes in the AD spectrum.MethodsIn this retrospective cohort study, we enrolled participants on the AD spectrum who were positive on18F-florbetab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 50 publications
(73 reference statements)
0
1
0
Order By: Relevance
“…16S rRNA gene sequencing demonstrated that LB rectified the disturbed floras including Porphyromonadaceae, Lactobacillus and Escherichia at the genus level ( Si et al, 2022 ). From another perspective, previous studies have indicated the intensely adverse influence of insomnia on cognitive functions of AD patients ( Bubu et al, 2017 ; Pak et al, 2020 ; Yoon et al, 2023 ). Therefore, LB may ameliorate impaired cognitive functions of AD patients directly through maintaining the gut microbiota homeostasis or indirectly through alleviation of sleep problems.…”
Section: Herbal Medicine and Admentioning
confidence: 99%
“…16S rRNA gene sequencing demonstrated that LB rectified the disturbed floras including Porphyromonadaceae, Lactobacillus and Escherichia at the genus level ( Si et al, 2022 ). From another perspective, previous studies have indicated the intensely adverse influence of insomnia on cognitive functions of AD patients ( Bubu et al, 2017 ; Pak et al, 2020 ; Yoon et al, 2023 ). Therefore, LB may ameliorate impaired cognitive functions of AD patients directly through maintaining the gut microbiota homeostasis or indirectly through alleviation of sleep problems.…”
Section: Herbal Medicine and Admentioning
confidence: 99%